A novel performance monitoring framework for health research systems: experiences of the National Institute for Health Research in England - Hallsworth Michael; El Turabi Anas; Ling Tom; Grant Jonathan (BMC, 2011)
Abstract Background The National Institute for Health Research (NIHR) was established in 2006 with the aim of creating an applied health research system embedded within the English National Health Service (NHS). NIHR sought to implement an approach for monitoring its performance that effectively linked early indicators of performance with longer-term research impacts. We attempted to develop and apply a conceptual framework for defining appropriate key performance indicators for NIHR. Method Following a review of relevant literature, a conceptual framework for defining performance indicators for NIHR was developed, based on a hybridisation of the logic model and balanced scorecard approaches. This framework was validated through interviews with key NIHR stakeholders and a pilot in one division of NIHR, before being refined and applied more widely. Indicators were then selected and aggregated to create a basket of indicators aligned to NIHR's strategic goals, which could be reported to NIHR's leadership team on a quarterly basis via an oversight dashboard. Results Senior health research system managers and practitioners endorsed the conceptual framework developed and reported satisfaction with the breadth and balance of indicators selected for reporting. Conclusions The use of the hybrid conceptual framework provides a pragmatic approach to defining performance indicators that are aligned to the strategic aims of a health research system. The particular strength of this framework is its capacity to provide an empirical link, over time, between upstream activities of a health research system and its long-term strategic objectives.